Cellular and Molecular Insights Into the Etiology of Subfertility/Infertility in Crossbred Bulls (Bos taurus × Bos indicus): A Review - Kumaresan, Arumugam; Elango, Kamaraj; Datta, Tirtha Kumar; Morrell, Jane M. (Frontiers in Cell and Developmental Biology, 2021)
Crossbreeding of indigenous cattle (Bos indicus) with improved (Bos taurus) breeds gained momentum and economic relevance in several countries to increase milk production. While production performance of the crossbred offspring is high due to hybrid vigour, they suffer from a high incidence of reproductive problems. Specifically, the crossbred males suffer from serious forms of subfertility/infertility, which can have a significant effect because semen from a single male is used to breed several thousand females. During the last two decades, attempts have been made to understand the probable reasons for infertility in crossbred bulls. Published evidence indicates that testicular cytology indices, hormonal concentrations, sperm phenotypic characteristics and seminal plasma composition were altered in crossbred compared to purebred males. A few recent studies compared crossbred bull semen with purebred bull semen using genomics, transcriptomics, proteomics and metabolomics; molecules potentially associated with subfertility/infertility in crossbred bulls were identified. Nevertheless, the precise reason behind the poor quality of semen and high incidence of sub-fertility/infertility in crossbred bulls are not yet well defined. To identify the underlying etiology for infertility in crossbred bulls, a thorough understanding of the magnitude of the problem is needed and an overview of the prior art; however, such systematically reviewed information is not available. Therefore, the primary focus of this review is to compile and analyze earlier findings on crossbred bull fertility. In addition, the differences between purebred and crossbred males in terms of testicular composition, sperm phenotypic characteristics, molecular composition, environmental influence and other details are described; future prospects for research on crossbred males are outlined.